Efektivitas Audit Tool And Linked Archived System (Atlas) Dalam Menganalisis Kecurangan Pada Laporan Keuangan - Audy Daewoo (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The progression of digitalization within information technology has had a profound impact on various facets of life, particularly in the realm of auditing. The contemporary audit procedures are predominantly computer-based, exemplified by applications such as ATLAS. Developed with the objective of facilitating the audit process in accordance with prevailing standards, the ATLAS application represents a notable instance of this technological shift. This study is undertaken to evaluate the efficacy of the ATLAS application in scrutinizing fraudulent activities within financial statements. Qualitative research employing a descriptive approach serves as the chosen methodology for this study. The research draws insights from theoretical frameworks, prior research findings, and interviews conducted with staff auditors from a Public Accounting Office. Collected data is thoroughly examined, leading to the formulation of conclusions. The research findings affirm the effectiveness of the ATLAS application in aiding auditors in the analysis and identification of fraud within client financial statements. However, it is emphasized that the responsibility for pursuing further action on identified fraud does not fall within the domain of financial statement audits but rather aligns with the purview of investigative audits. Financial statement audits primarily focus on delivering statements, opinions, or assessments regarding the fairness of the presentation of financial statements for respective clients.